Padrões Ecogeográficos da interação parasita-hospedeiro: uma abordagem EcoHealth - Silva, Guilherme Gonzaga da (2023)
One of the most recognizable biogeographic patterns is the latitudinal gradient of biodiversity. From it, several other patterns have been derived and studied for decades. The interactions among organisms are also subject to these patterns. Of particular interest are the parasitic organisms, since many of these organisms act as vectors of pathogens of medical and veterinary interest. The close dependence of parasites on their hosts generates particularities in the way these organisms respond to variations in different biotic and abiotic factors. The elucidation of these elements can subsidize innovative interdisciplinary approaches such as ecohealth, which seeks to integrate human, animal, and environmental health. Thus, the present thesis aimed to explore the bioclimatic factors at macroscale and the role of population distribution dynamics and diversity of hosts and vectors in host-parasite interactions. The results added evidence of the role of abiotic gradients on parasites at a broader scale and indicate that different modes of parasitic lifestyles can lead to different responses to these factors. It was also demonstrated that host biodiversity influences the transmission of pathogens in systems involving vectors. However, the inclusion of multiple host-parasite systems can hinder the study of these interactions due to the underlying complexity of population dynamics.